Un Fragment de la Salmòdia copta conservat a la Biblioteca Episcopal de Vic - Vicens i Pedret, Xavier M. (Miscel·lània litúrgica catalana, 2013)
In the Biblioteca Episcopal de Vic is preserved a manuscript sheet coming from a coptic paper liturgical book. The preserved text is a fragment of the Christmas psalmody of Khoiak, the month of the coptic calendar in which Christmas is celebrated. The Psalmody is an ensemble of preparatory prayers before receiving Eucharist, said the night before the celebration. It is not part of the eucharistical liturgy neither of the office, although it can remind of it due to its structure alternating psalms and hymns. It is recorded in a proper liturgical book.